LENGTH-WEIGHT RELATIONSHIP OF MEGALASPIS CORDYLA (LINNAEUS,1758) ALONG NORTH WEST COAST OF INDIA. - JAISWAR, A. K.; ACHARYA, P. (Journal of Indian Fisheries Association, 2015)
Total length and total weight relationship of Megalaspis cordyla (Linnaeus, 1758) a carangid fish,along North west coast of India has been worked oul. The fish is an ideal one, growing by weight @ cube of its length, isometrically, retaining its specific hody shape throughout its life. The relastionship is W = 0.00906279 L 2·9824152, where "W " is total weight of fish in g and "L" :represents total lrngth in cm.